Poly-Drug Use And Violent Crime Among Offenders In The State Of Penang: A Cross-Sectional Study - Krishnan, Harinderan (2020)
Amphetamine-type stimulant (ATS) use is associated with a myriad of health problems such as HIV transmission, risky sexual behaviours, psychological problems and criminal behaviours. Though the relationship between illicit drug use and crime is poorly investigated in Malaysia, findings from international perspectives show that people who use drugs (PWUDs) are more likely to be detained for criminal offences. This study determined the relationship between ATS poly-drug use and crime in a cohort of police detainees who were caught for criminal offences in the state of Penang. A total of 149 police detainees with current illicit drug use history were recruited through purposive and convenience sampling for this cross-sectional study. The surveys were conducted through face-to-face interviews with a semi-structured questionnaire.